In situ studies of butyronitrile adsorption and hydrogenation on Pt/Al2O3 using attenuated total reflection infrared spectroscopy - Ortiz-Hernandez, Ivelisse (Langmuir : the ACS journal of surfaces and colloids, 2007)
The adsorption and hydrogenation of butyronitrile (BN) in hexane on a 5% Pt/Al2O3 catalyst has been studied using in situ attenuated total reflection infrared (ATR-IR) spectroscopy. ATR-IR measurements were conducted on thin ( approximately 10 mum) films of catalyst deposited on Ge wave guides. Multivariate analysis involving classical lease-squares (CLS) and partial least-squares (PLS) modeling was used to aid in the interpretation of the spectroscopic data. During the adsorption of BN over a concentration range from 4 to 40 mM in hexane, no clear evidence for adsorbed N-bound end-on species could be detected. However, a feature at approximately 1635-1640 cm-1 indicated the presence of an adsorbed imine species, with the C=N group existing in a tilted configuration involving a strong degree of pi interaction with the surface. This assignment is bolstered by the detection of N-H stretching bands that are consistent with imine vibrations. This imine-type intermediate is very prominent and shows transient behavior in the presence of solution-phase hydrogen, suggesting that, once formed, it can be converted into amine products that adsorb on the catalyst surface. Evidence for amine formation was observed in the form of N-H stretching and NH2 bending vibrations, with assignments confirmed through comparison studies of butylamine adsorption under identical conditions. Comparisons between Pt/Al2O3 and Al2O3 suggest that there may be some adsorption of these amines on the support surface. The mechanistic implications with regard to heterogeneous nitrile hydrogenation on transition metals under mild conditions are briefly discussed in light of these findings